Experimental study on creep failure characteristics of coal mass under multistage stress and construction of prediction model - Yang, Yiran; Li, Yanzhong; Yuan, Kekuo; Lu, Zidong; Li, Gang (Frontiers in Earth Science, 2023)
The creep and failure mode of stratified coal is complex and hard to predict, this is strongly related to the internal stratified structure generated during coal forming. In this study, the inner stratified structure of coal during creep was mainly considered. Experiment was used to analyze the evolution relationship between the key creep parameters and the inner stratified structure. The creep failure characteristics of coal under complex stress were obtained. A neural network model was established to predict creep behavior, and the output results were controlled by smoothing and tracking to reduce the error. Results showed that the creep characteristics of coal with various types of stratified structure were different, and the key parameters such as creep variable, steady creep stage and creep rate had nonlinear relationship with stress. The dual control neural network model constructed in the study has improved the accuracy and stability of the model, which has guidance and reference value for the study of creep failure mechanism and creep behavior prediction of stratified coal.